Stupid things I won't do when I'm old : a highly judgmental, unapologetically honest accounting of all the things our elders are doing wrong - Petrow, Steven; Henry, Roseann Foley (Citadel Press, Kensington Publishing Corp., 2021)
An award-winning journalist, in this essential - and hilarious - guide, addresses the fears, frustrations and stereotypes that accompany aging, offering a blueprint for the new old age, and an understanding that aging and illness are not the same.